Does Debridement of Intracranial Disease in Acute Invasive Fungal Sinusitis Improve Survival? - Huang, Alice E.; Lee, Christine K.; Nayak, Jayakar V.; Hwang, Peter H.; Patel, Zara M.; Fernandez-Miranda, Juan C.; Chang, Michael T. (Journal of Neurological Surgery Part B: Skull Base, 2025)
Intracranial (IC) extension is a poor prognostic factor for acute invasive fungal sinusitis (IFS). There are no studies on the role of IC debridement in the setting of rhinocerebral IFS.We retrospectively reviewed patients with rhinocerebral IFS confirmed on imaging who underwent surgical management. Patients who underwent sinonasal debridement only (reference group) were compared with those who underwent sinonasal and IC debridement (IC group). The primary outcome was overall survival. Univariate analysis and logistic regression were performed to assess for differences in clinical characteristics between the treatment groups and predictive factors of survival.Twenty-nine patients were included in the study, with 10 patients in the IC group and 19 patients in the reference group. There were no significant differences in patient demographics or predisposing conditions between the groups. Regarding IC extent of fungal disease, there were no significant differences in rates of dural, leptomeningeal, or parenchymal involvement; cavernous sinus extension; or cisternal cranial nerve involvement. The IC group had significantly more IC abscesses (60%) than the reference group (5%, p = 0.002). At the time of the most recent follow-up (month, year), 30% (n = 3) of the IC group, and 79% (n = 15) of the reference group had died (p = 0.02). The Cox proportional hazards model demonstrated a 93% reduction in the risk of death with IC debridement when adjusting for all covariables (p = 0.004).This study is the largest series to examine neurosurgical management of rhinocerebral IFS, demonstrating possible survival benefit with IC debridement in select patients and with highly specialized surgical expertise.
Keywords: invasive fungal sinusitis; skull base surgery; endoscopic sinus surgery